2022
DOI: 10.1097/iae.0000000000003456
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatic Vitreolysis Versus Pars Plana Vitrectomy in Focal Symptomatic Vitreomacular Traction Syndrome

Abstract: Purpose: To compare pneumatic vitreolysis and pars plana vitrectomy in the management of focal symptomatic vitreomacular traction (VMT).Method: Patients aged 18 years or older, with idiopathic focal symptomatic VMT and best-corrected visual acuity ,20/40, without any other retinal pathology were randomized to undergo pneumatic vitreolysis (Group 1) or pars plana vitrectomy (Group 2). The primary outcome measure was resolution of traction confirmed with optical coherence tomography at 3 months. Secondary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Pars plana vitrectomy is now considered a golden standard for VMT treatment with favorable anatomical and visual outcomes. 2,3,10 In this study, postoperative CMT was significantly decreased from baseline, with most eyes completing the restoration of the normal foveal depression and subretinal fluid resolution. Moreover, significant visual improvement was achieved after PPV, including nearly one half improving ≥ two Snellen lines, which was consistent with the previous studies, 4,5 justifying the efficacy of surgical treatment in facilitating anatomical and visual recovery for VMT patients.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Pars plana vitrectomy is now considered a golden standard for VMT treatment with favorable anatomical and visual outcomes. 2,3,10 In this study, postoperative CMT was significantly decreased from baseline, with most eyes completing the restoration of the normal foveal depression and subretinal fluid resolution. Moreover, significant visual improvement was achieved after PPV, including nearly one half improving ≥ two Snellen lines, which was consistent with the previous studies, 4,5 justifying the efficacy of surgical treatment in facilitating anatomical and visual recovery for VMT patients.…”
Section: Discussionmentioning
confidence: 52%
“…Although pneumatic vitreolysis and intravitreal injection of ocriplasmin are less invasive, PPV is considered as the gold standard for the treatment for symptomatic VMT because of its high success rate and favorable visual improvement. 2,3…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…of macular holes Success rate of macular hole closure Follow-up period Total no. of diagnosed VMT cases VMT release Kumar et al [ 29 ] Prospective PV 15 63.8 ± 8.38 0.80 ± 0.26 0.70 ± 0.49 (20/100 SE) 15 4 (27%) 3 months 15 12 (80%) PPV 15 68.33 ± 8.19 0.904 ± 0.44 0.47 ± 0.26 (20/59 SE) 15 15 (100%) 3 months 15 15 (100%) Alreshaid et al [ 30 ] Retrospective PPV 11 Not reported 0.81 ± 0.24 0.64 ± 0.26 10.27 ± 4.63 months 11 11 (100%) Ocriplasmin 8 Not reported 0.53 ± 0.29 0.52 ± 0.29 N/A N/A 3.87 ± 2.66 8 5 (62.5%) Anderson et al [ 21 ] Prospective PPV 5 …”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference (risk ratio = 0.87, 95% CI 0.73–1.03, p = 0.11) in the VMT release rate between the two groups in terms of therapeutic efficacy (Fig. 12 ); however, only one study [ 29 ] compared the MH closure rate and showed that PPV had a higher rate of MH closure (risk ratio = 3.44, 95% CI 1.57, 7.58, p = 0.002), as shown in the funnel plot in Fig. 13 .…”
Section: Resultsmentioning
confidence: 99%